2001
DOI: 10.1038/sj.bmt.1703012
|View full text |Cite
|
Sign up to set email alerts
|

Degree of fatness after allogeneic BMT for childhood leukaemia or lymphoma

Abstract: Summary:Excess fatness is frequent after childhood ALL treated without BMT. We measured the whole-body percent fat by dual-energy X-ray absorptiometry and the bodymass index (weight/height 2 (kg/m 2 ), BMI) in 25 survivors of childhood leukaemia or lymphoma (21 with ALL) who had received TBI and allogeneic BMT a median of 8 years ago (range 4-13). Adjusted for sex and age, the mean BMI was slightly but significantly reduced (0.4 s.d. below predicted) and the whole-body percent fat was significantly increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
(42 reference statements)
1
28
0
Order By: Relevance
“…Although cystatin C gives a more crude GFR estimate than does 51 Cr-EDTA analysis, it is probably more accurate than creatinine, as it is independent of muscle mass [14,15]. This may be particularly important in patients who have undergone SCT including TBI, as they often develop abnormalities in body composition with a proportionally reduced lean body mass [16]. We found chronic renal impairment (GFR<85 ml/min per 1.73 m 2 ) in two patients (11%), which is in line with the prevalence of impaired renal function reported by Kist-van Holthe et al [4], who in a prospective study found chronic renal impairment (in those > 2 years of age, this was defined as GFR<85 ml/min per 1.73 m 2 ) in four of 41 (10%) longterm survivors, 42% of whom had received TBI 5 years after allogeneic SCT.…”
Section: Glomerular Functionmentioning
confidence: 97%
“…Although cystatin C gives a more crude GFR estimate than does 51 Cr-EDTA analysis, it is probably more accurate than creatinine, as it is independent of muscle mass [14,15]. This may be particularly important in patients who have undergone SCT including TBI, as they often develop abnormalities in body composition with a proportionally reduced lean body mass [16]. We found chronic renal impairment (GFR<85 ml/min per 1.73 m 2 ) in two patients (11%), which is in line with the prevalence of impaired renal function reported by Kist-van Holthe et al [4], who in a prospective study found chronic renal impairment (in those > 2 years of age, this was defined as GFR<85 ml/min per 1.73 m 2 ) in four of 41 (10%) longterm survivors, 42% of whom had received TBI 5 years after allogeneic SCT.…”
Section: Glomerular Functionmentioning
confidence: 97%
“…28 Lower BMI were found by Nysom et al 32 in patients with childhood leukemia and lymphomas treated with TBI than in patients without TBI, which suggests that either TBI or more severe delayed side effects after HSCT alter body weight, and possibly body composition. Nyson et al 32 found that cranial irradiation leads to muscle loss and body fat in children. Couto-Silva et al 33 found that children with TBI had lower BMIs at 2 and 5 years post-HSCT than patients who were not treated with TBI.…”
Section: Effects Of Treatmentmentioning
confidence: 99%
“…Although overweight/obesity in adult survivors of childhood ALL has been well evaluated, no longitudinal study that investigated metabolic abnormalities in survivors of childhood SCT has been reported, 15,16 and the mechanism of these conditions has not been completely understood. A longitudinal retrospective study of a cohort of adult survivors of childhood SCT was performed to determine whether adult survivors are at risk for overweight/obesity, metabolic abnormalities and fatty liver and whether this risk is associated with CRT or other factors used in the treatment of SCT.…”
Section: Introductionmentioning
confidence: 99%